First Detection and Genome Sequencing of SARS-CoV-2 Lambda (C.37) Variant in Symptomatic Domestic Cats in Lima, Peru - Schiaffino, Francesca; Ferradas, Cusi; Jara, Luis M.; Salvatierra, Guillermo; Dávila-Barclay, Alejandra; Sanchez-Carrion, Camila; Ulloa, Alexandra; Mascaro, Lucero; Pajuelo, Monica J.; Guevara Sarmiento, Luis; Fernandez, Manolo; Zimic, Mirko (Frontiers in Veterinary Science, 2021)
The role of domestic cats in the dynamics of SARS-CoV-2 remains poorly characterized, especially in epidemiologic contexts of countries with high viral transmission. Here we report the first evidence of SARS-CoV-2 Lambda variant of interest in symptomatic domestic cats whose owners were diagnosed with COVID-19 in Lima, Peru, providing evidence that transmission of this new variant into domestic cats is occurring. More epidemiological studies are required to further characterize the role of domestic animals in the transmission dynamics of SARS-CoV-2.